2011
DOI: 10.22458/urj.v3i2.149
|View full text |Cite
|
Sign up to set email alerts
|

Pycnogonida from Costa Rica collected by Scuba Diving

Abstract: The knowledge of the pycnogonid fauna of Costa Rica is poor. This is the first report on Pycnogonida collected by scuba diving from both oceans of Costa Rica. Nine species from the Caribbean side and one from the Pacific coast are reported. We add eight species to the Caribbean fauna and one to the Pacific fauna of Costa Rica. No species new to science were encountered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Spanish coast: Malaga, Alboran Sea (Munilla, 1991); Chafarinas Islands, Alboran Sea (Munilla and Nieto, 1999); Ceuta (Tarragona San Vicente, 2000:2005). Italian coast: Naples (Dohrn,1881;Munilla, 1994); Catania, Sicily Island (Krapp, 1973); Costa d'Argento-Southern Tuscany (Vignoli et al, 2006); Giglio Island (Lehmann et al, 2014). Croatian coast: Islet of Banjole, Adriatic Sea (Krapp-Schickel and Krapp, 1975); Rovinj, Adriatic Sea (Schüller, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spanish coast: Malaga, Alboran Sea (Munilla, 1991); Chafarinas Islands, Alboran Sea (Munilla and Nieto, 1999); Ceuta (Tarragona San Vicente, 2000:2005). Italian coast: Naples (Dohrn,1881;Munilla, 1994); Catania, Sicily Island (Krapp, 1973); Costa d'Argento-Southern Tuscany (Vignoli et al, 2006); Giglio Island (Lehmann et al, 2014). Croatian coast: Islet of Banjole, Adriatic Sea (Krapp-Schickel and Krapp, 1975); Rovinj, Adriatic Sea (Schüller, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Previously records of Callipallene tiberi (Dohrn, 1881) from the Mediterranean Sea are from the western and central basins (Dohrn, 1881;Krapp, 1973;Krapp-Schickel and Krapp, 1975;Schüller, 1989;Munilla, 1991Munilla, ,1994Munilla and Nieto, 1999;San Vincente, 2000:2005;Vignoli et al, 2006;Lehman et al, 2014). There is no record of C. tiberi from the eastern Mediterranean as yet.…”
Section: Introductionmentioning
confidence: 97%
“…Here P. geayi was recorded from depths of 0-2 m. All specimens were caught in tide pools in intertidal sandstone reefs during low tide, extending the bathymetric distribution shoreward for this species. Previous studies realized in other countries (French Guiana and Puerto Rico) showed that bathymetric distribution of P. geayi ranges from depths of 5-11 m (Hedgpeth 1947;Krapp & Viquez 2011).…”
mentioning
confidence: 95%
“…The genus is composed of three species: Pentapycnon bouvieri Pushkin, 1993 andP. charcoti Bouvier, 1910 (Antarctic andSubantarctic regions), and P. geayi Bouvier, 1911 (Caribbean Sea to the Southwestern Atlantic Ocean) (Bouvier 1911;Hedgpeth 1948;Stock 1975Stock , 1992Child 1995;Krapp & Viquez 2011). The present record of P. geayi is the first for the state of Ceará, and therefore fills a gap in this species' distribution along the Brazilian coast between the states of Pará and Rio Grande do Norte.…”
mentioning
confidence: 99%
See 1 more Smart Citation